2017
DOI: 10.1017/s002221511700113x
|View full text |Cite
|
Sign up to set email alerts
|

Post-adenoidectomy quality of life in children with refractory chronic rhinosinusitis

Abstract: Adenoidectomy is a simple, first-line surgical procedure for managing paediatric chronic rhinosinusitis refractory to maximal medical therapy and leads to an improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
6
0
5
Order By: Relevance
“…Adenoidectomy had a 47% success rate, while ESS had a 77% success rate 2354 . A 2017 prospective interventional study in 66 children aged 4‐12 years with refractory CRS showed improvement in QoL scores after adenoidectomy when compared to baseline in 88% of children using the SN‐5 instrument 2355 . Because there is a significant overlap of symptoms between CRS and chronic adenoiditis, the diagnosis before surgery must rely on objective measures such as nasal endoscopy or CT scan.…”
Section: Pediatric Rhinosinusitismentioning
confidence: 99%
“…Adenoidectomy had a 47% success rate, while ESS had a 77% success rate 2354 . A 2017 prospective interventional study in 66 children aged 4‐12 years with refractory CRS showed improvement in QoL scores after adenoidectomy when compared to baseline in 88% of children using the SN‐5 instrument 2355 . Because there is a significant overlap of symptoms between CRS and chronic adenoiditis, the diagnosis before surgery must rely on objective measures such as nasal endoscopy or CT scan.…”
Section: Pediatric Rhinosinusitismentioning
confidence: 99%
“…Die Datenerhebung der Interventionsgruppe erfolgte am Operationstag (präoperativ) und auf postalischem Weg 3-4 Monate postoperativ. Dieser Zeitraum wurde als günstig erachtet, da sich in der Literatur zu späteren Zeitpunkten keine relevanten Veränderungen des kurzfristigen Operationsergebnisses zeigten [14,15,18,19] "Kiddy-KINDL"-Fragebogen Als geeignetster Fragebogen erschien der "Kiddy-KINDL"-Fragebogen, welcher durch Bullinger et al 1994 erstmals deutschsprachig publiziert und speziell für den Einsatz in der Pädiatrie im Vorschulalter konzipiert wurde. Er zeichnet sich durch eine hohe Reliabilität und befriedigende konvergente Validität aus [20,21].…”
Section: Materials Und Methodenunclassified
“…Obwohl es angesichts der vielfältigen körperlichen Einschränkungen der Kinder naheliegend ist, dass auch die kindliche Lebensqualität beeinträchtigt wird, gibt es hierzu noch wenige Daten. Vorliegende Studien zur Lebensqualität in Abhängigkeit von schlafbezogenen Atemstörungen und oberen Atemwegsinfektionen weisen auf einen kurz-und langfristigen Benefit in der krankheitsbezogenen Lebensqualität hin [9][10][11][12][13][14][15][16]. Ob jedoch auch die allgemeine Lebensqualität durch das Krankheitsbild relevant beeinflusst wird und ob diese durch Adenotomie sowie Adenotonsillotomie (ATT) relevant beeinflusst wird, ist bisher kaum untersucht.…”
Section: Introductionunclassified
“…1 In this month's issue of The Journal of Laryngology & Otology, a study by Bettadahalli and Chakravarti demonstrates an improvement in quality of life following adenoidectomy for paediatric chronic rhinosinusitis. 2 Whether the improvement seen following adenoidectomy is related to adenoiditis, or is due to the elimination of the contribution of the adenoids to sinus disease, is unclear. Nonetheless, there is increasing evidence that within the setting of paediatric chronic rhinosinusitis, the adenoid acts as a reservoir of pathogenic bacteria through the formation of biofilms, rather than a source of obstruction per se.…”
mentioning
confidence: 99%
“…The exact role of the adenoid in paediatric chronic rhinosinusitis is still under debate 1 . In this month's issue of The Journal of Laryngology & Otology , a study by Bettadahalli and Chakravarti demonstrates an improvement in quality of life following adenoidectomy for paediatric chronic rhinosinusitis 2 . Whether the improvement seen following adenoidectomy is related to adenoiditis, or is due to the elimination of the contribution of the adenoids to sinus disease, is unclear.…”
mentioning
confidence: 99%